Analisis Teknik Membaca Memindai Siswa Kelas 5 SD - Figo Pratama Chandra; Pradika Alim Zulemil; Chandra Chandra; Ari Suriani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to analyze the effectiveness of applying the case method to the reading comprehension abilities of 5th grade elementary school students using the case study method. The scanning reading technique is a reading method that focuses on quickly finding specific information in text. This research uses a case study approach to gain in-depth insight into the application of scanning reading techniques in grade 5 elementary school students. The research subjects were 5th grade elementary school students in Kampung Jati. Data was collected through observation, interviews, and reading comprehension tests before and after applying the scanning reading technique. The results of the research show that the application of scanning reading techniques among 5th grade elementary school students in Kampung Jati is still relatively low, especially in terms of reading speed and accuracy. This case study also reveals that students need to increase motivation and interest in reading activities.